2011
DOI: 10.4314/afrrev.v5i4.69266
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria Parasites among Nnamdi Azikwe University Students and Anti-Malaria Drug Use

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 4 publications
6
5
1
Order By: Relevance
“…From our findings, higher prevalence rate were seen in males than females: out of 75 males, 68(90.7%) of them where infected, and of the 75 females sampled, 67(89.3%) of them of where infected although there was no significant difference between prevalence of malaria between males and females. This was in agreement with the finding of Ezugbo et al [21] who reported that prevalence of malaria among the male gender was higher than of the female. Akanbi et al [22] also reported that the cause of higher prevalence observed in male could be due to the fact that they exposed their bodies more than females when the weather was hot and thus increased the chances of being bitten by the mosquitoes.…”
Section: Discussionsupporting
confidence: 94%
“…From our findings, higher prevalence rate were seen in males than females: out of 75 males, 68(90.7%) of them where infected, and of the 75 females sampled, 67(89.3%) of them of where infected although there was no significant difference between prevalence of malaria between males and females. This was in agreement with the finding of Ezugbo et al [21] who reported that prevalence of malaria among the male gender was higher than of the female. Akanbi et al [22] also reported that the cause of higher prevalence observed in male could be due to the fact that they exposed their bodies more than females when the weather was hot and thus increased the chances of being bitten by the mosquitoes.…”
Section: Discussionsupporting
confidence: 94%
“…This could be due to a number of reasons such as time of survey (carried out in the dry season), regular fumigation of the school hostels to destroy mosquito breeding habitants amongst others. The findings of this study is in contrast to that reported in other studies carried out in Universities in South eastern (7,21) and western parts of the country (22) where more than half and almost half of the students were found infected with falciparum malaria respectively. This disparity in prevalence could be due to difference in effort put towards clearing the vegetation around the hostels or the period of the survey.…”
Section: Burden Of Malaria Amongst the Respondentscontrasting
confidence: 56%
“…Malaria infection impairs physical and mental development in children and as a result of this, it is a major cause of death due to anaemia in young children. More so, malaria is known to have a negative impact on learning in children resulting in absenteeism and ultimately leading to poor academic performance (7,8). In areas of high and stable transmission, people tend to develop immunity following repeated infections, so that the population at greater risk of malaria are young children who had not yet had multiple exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Among undergraduate students in Nnamdi Azikiwe University Awka, Ezugbo-Nwobi et al . (2011) reported a 64% prevalence of malaria parasite infestation similar to the findings of this study.…”
Section: Discussionmentioning
confidence: 99%